Increased Expression of Apoptosis-Associated Proteins in Puromycin Aminonucleoside Nephrosis - Viera, Ninoska; Pedreáñez, Adriana; Romero, Maritza; Rincón3Jaimar; Mosquera, Jesús (Investigación Clínica, 2009)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:"Caslon224 Bk BT"; panose-1:0 0 0 0 0 0 0 0 0 0; mso-font-alt:"Times New Roman"; mso-font-charset:0; mso-generic-font-family:roman; mso-font-format:other; mso-font-pitch:auto; mso-font-signature:0 0 0 0 0 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–>Increased apoptosis has been reported in acute puromycin aminonucleoside nephrosis (PAN). The aim of this study was to investigate if increased apoptosis is related to increased expression of apoptosis-associated proteins (AAP) in this model of nephrosis. Sprague-Dawley rats were made nephrotic by intraperitoneal injection of one dose of puromycin aminonucleoside. Renal tissues were obtained at 1, 2 and 7 weeks after injection and apoptosis was investigated by TUNEL and by electron microscopy. Fas, Fas ligand, p53, Bax and Bcl-2 expressions were analyzed by the respective monoclonal and polyclonal antibodies, using indirect immunofluorescence. In the glomerulus of nephrotic animals, increased apoptosis was accompanied with increased expression of p53, Fas and Bax. In the interstitium, high expression of apoptosis, Fas, Fas-L and Bax were observed and in tubules increased apoptosis was accompanied with increased expression of p53, Fas and Fas-L. Bcl-2 was increased in interstitium and tubules during PAN. The incidence of apoptosis during PAN was correlated with the expression of AAP in glomerulus (p53), interstitium (Fas, Fas-L and Bax) and tubules (Fas, Fas-L, p53 and Bcl-2). There was correlation between Fas and Fas-L expression in interstitium and tubules. About 4% of glomerular and 25% of tubular p53 positive cells were apoptotic cells. The data suggest that increased local expression of AAP could contribute to renal apoptosis in the glomerular, interstitial and tubular compartments during this experimental model of nephrosis